In vitro characterization of phytophthora palmivora butler isolated from avocado (persea americana miller) fruit rot - Nemenzo, Dyan S. (2008)
Phytophthora palmivora Butler was isolated from avocado fruit rot lesion. Pathogenicity test was carried out on healthy avocado fruits and result confirmed the pathogenic association of the organism with avocado. Morphological and cultural characterization on the isolate were done in vitro. Colony growth on Carrot Agar produced stellate pattern with tufted to appressed serial mycelium. The conspicuously papillate and caduceus sporangia have an average length of 53.473 10.49m, breadth of 35.73 5.10m, length-breadth ratio of 1.53 0.22, short pedicel of 3.082 1.28m, papilla length of 5.373 2.05m, and papilla breadth of 7.473 1.91m. the globose chlamydospores have a mean diameter of 30.38 6.41m. continuous light and alternating 12 hr light: 12hr darkness have greatest colony growth and most abundant spore production tan continuous darkness. Growths in pH 6-8 were comparable but pH 7 yielded the most number of spores. Daytime temperature of 270C to 290C had markedly wider growth than in 220C - 240C but spore counts did not vary between the treatments. Natural media such as Carrot Agar, Lima Bean Agar, and V-8 Juice Agar produced bigger colony growths and sporangial production than Potato Dextrose Agar, and Czapeck Dox Modified Agar and Malt Extract Agar. Since the pathogenicity test showed that wounds can enhance fruit rot infection, it is recommended that abrasions or injuries on fruits be avoided to minimize if not deter disease occurrence on fruits
Thesis (BS Biology) -- University of the Philippines Mindanao, 2008
Keywords: Avocado; Avocado fruit rot; Avocado -- Cultural characteristics; Avocado -- Morphology; Avocado -- Importance; Avocado -- Production; Avocado -- Diseases; Inoculation; Reisolation; Avocado -- Safekeeping; Avocado fruits. -- Infection